National Land-Use Planning in America: Something Whose Time Has Never Come - Jerold S. Kayden (Washington University Journal of Law & Policy, 2000)
This Essay discusses the legal and institutional structure for land use planning and regulation in the United States, concluding that the national government has not and does not practice what would constitute national land-use planning as that term is commonly understood in the United States and abroad.
Keywords: Land use; Regional planning